Polyphenolic promiscuity, inflammation-coupled selectivity: Whether PAINs filters mask an antiviral asset - Sheridan, Rick; Spelman, Kevin (Frontiers in Pharmacology, 2022)
Two years into the covid-19 pandemic, the world still lacks affordable, effective, non-prescription antivirals. Even outside the pandemic, few types of viral infections can be treated with an effective antiviral. Antiviral drug development challenges medicinal ‬chemists because many compounds that effectively inhibit viral enzymes often inhibit cellular enzymes as well. In order to achieve specificity, chemists usually seek unique chemical structures that satisfy the “lock-and-key” mechanism of ligand-enzyme binding. ‬ ‪ Based on results accumulated by several research groups over the past two decades‬, we ‪propose an antiviral specificity model, entirely removed from "lock-and-key", but rather rooted in the human metabolism’s activation of polyphenol compounds from plants. at sites of pathology-induced inflammation. Outside of these pathologic sites, polyphenols remain‬ in a latent, glucuronidated form following ordinary metabolism, and are quickly eliminated from circulation. However at sites of inflammation, polyphenols promiscuously bind viral and human enzymes alike. These two modalities jointly, called the deglucuronidation-through-inflammation mechanism provide the selectivity that antiviral therapies demand. The deglucuronidation-through-inflammation mechanism would apply to viral diseases that induce localized inflammation such as Dengue, Chikungunya, Influenza, and SARS-CoV-2. Verification of its efficacy against these viruses would open up a broadly-accessible class of plant-extractable compounds for therapeutic use.